Stability Testing of Compounding Capsule Combination between Paracetamol and Tramadol in a Private Hospital Semarang - Shirley Candra Kurniawan; Michael Raharja Gani; Sri Hartati Yuliani (Journal of Fundamental and Applied Pharmaceutical Science, 2020)
A combination of Paracetamol and Tramadol is used in mild to severe pain management. In a private Hospital Semarang, this combination is included in fast-moving drugs that it is frequently compounded and prepared in advance. The study aims to determine Beyond Use Date (BUD) in compounding capsules combination between Paracetamol and Tramadol samples. Beyond Use Date is a time limit indicating that a medicine beyond the expiration date must not be used and determined based on the results of stability testing. Samples were stored for 14 days in a tightly closed container far from direct sunlight in room temperature without AC (280C) and without silica gel, room temperature with AC (250C) without silica gel, and room temperature with AC (250C) with silica gel. Furthermore, samples underwent physical and chemical stability testing. Physical stability testing was conducted using organoleptic testing by observing direct changes from the powder color in capsules, capsules form, and scent on the samples. Meanwhile, chemical stability testing was conducted by determining the content of active ingredient from the samples using reversed-phase HPLC method and C18 as the stationary phase, methanol and aquabidest (40:60) as the mobile phase, wavelength 271 nm, flow rate 0.6 mL/min and injection volume 10 μL. The result shows that samples were physically stable for being able to retain the original physical properties showed by consistent powder color and capsules form, and there was no available scent. However, the chemical stability testing method was unable to separate and quantify the content of Paracetamol, Tramadol, and formed degradation products. It can be concluded that Beyond Use Date based on organoleptic and chemical stability testing for 14 days of compounding capsules combination between Paracetamol and Tramadol could not be determined. Nevertheless, this study showed favorable storage conditions in a tightly closed container far from direct sunlight in Room Temperature with AC (250C) with Silica Gel.